HUKUM LINGKUNGAN - Ella Fahriza; Julpan Andri; Junita Sari; Muhammad Nur Alim; Naila Karima; Nurlia Nurlia (Nusantara Hasana Berdikari, 2022)
In Law Number 32 of 2009 concerning Protection and Management of the Environment, in Article 1 as follows: The environment is a unitary space with all objects, forces, conditions and living things, including humans and their behavior, which affect the continuity of life and welfare of humans and other living beings. Environmental management is an integrated effort to preserve environmental functions which includes policies for structuring, utilizing, developing, maintaining, recovering, monitoring, and controlling the environment. The method used in this research is normative legal research, namely legal research that puts law as a system of norms. Environmental management to preserve and develop a harmonious, harmonious and balanced environmental capability to support the implementation of environmentally sound sustainable development, according to Law Number 32 of 2009 concerning Environmental Protection and Management, has the following goals and objectives: a. Protect the territory of the Unitary State of the Republic of Indonesia from pollution and/or environmental damage; b. Ensure safety, health and human life; c. Ensuring the continuity of the life of living things and the preservation of the ecosystem; and others.